2004
DOI: 10.1055/s-2003-45234
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Therapeutic Ultrasound on Skeletal Muscle Regeneration Following Blunt Contusion

Abstract: Athletic trainers typically use therapeutic ultrasound to treat skeletal muscle contusion injuries. However, the structural outcomes underlying this treatment are not well understood. Our working hypothesis was that following a blunt contusion injury to the gastrocnemius muscle, ultrasound treatment would facilitate recovery, as indicated by changes in several biological markers of skeletal muscle regeneration. Eighty male Wistar rats (three-month) were studied. Following anesthetic administration, each animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 8 publications
0
12
0
2
Order By: Relevance
“…7,43,59 Other adjunctive therapies hold promise for improving muscle healing and limiting scar formation, but further research is needed to define their roles. 9,11,44,49,50,57,65 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,43,59 Other adjunctive therapies hold promise for improving muscle healing and limiting scar formation, but further research is needed to define their roles. 9,11,44,49,50,57,65 …”
Section: Resultsmentioning
confidence: 99%
“…In a recent study using a rat contusion model, daily therapeutic ultrasound had no effect on muscle healing or regeneration. 65 Earlier translational work demonstrated that pulsed ultrasound could promote satellite cell proliferation, although this modality did not have a significant effect on the overall morphological manifestations of muscle regeneration. 54 Finally, the combination of ultrasound and exercise showed no benefit to skeletal muscle regeneration after contusion injury.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its biological effects in acute and chronic inflammation are not well understood,2, 6, 7, 8 therapeutic ultrasound (TUS) has been recommended. Piedade et al 7 assessed the effects of pulsed application on lacerated gastrocnemius muscle of rats, and observed a significant increase in the number of myotubes in the regeneration zone 14 days after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that both TUS and muscle stretching are indicated for the treatment of muscle injury,2, 5, 6, 7, 8, 9 but there is still no consensus on when and how to prescribe them. Moreover, it is unclear whether the association between these therapeutic modalities can benefit the muscle regeneration mechanism.…”
Section: Introductionmentioning
confidence: 99%